Strategi Guru PPKn dalam Meningkatkan Motifasi Belajar Siswa yang Memiliki Nilai Rendah di SMA Budisatrya Medan - Nur Hidayah Hasibuan; Muhammad Iraqi Fauzi; Tri Bayu Armanda; Dyna MT Pasaribu; Abdi Nur Batubara (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to determine the role of PPKn teachers in increasing student learning motivation at SMA Budistrya Medan. This research is research that uses a qualitative approach. The data collection technique uses a questionnaire which contains the types of questions that will be distributed. The research subjects or informants involved in this research were teachers and students of Medan Budisatrya High School. The data analysis techniques used are data collection, data reduction, data display, and drawing conclusions. The results of this research indicate that the role of PPKn teachers is in increasing student learning motivation at SMA Budisatrya Medan. among others, giving objective numbers, giving prizes to students who win inter-class competitions and class champions, teachers giving praise to students who can answer questions given during lessons or when they get satisfactory grades after tests or assignments, giving punishments in the form of giving additional tasks, providing input to students whose achievements are still below standard. Obstacles faced by teachers in increasing student learning motivation.